RESEARCH OF THE BEHAVIOR PATTERN OF USERS OF EDUCATIONAL RESOURCES FOR LEARNING COMPUTER GRAPHICS PROGRAMS - Базилюк , Е. В.; Кармаліта , А. К.; Стрижова , О. П.; Горний , П. В. (Art and Design, 2023)
Purpose. Research of user experience with educational resources for studying computer graphics programs; determination of user requirements for relevant educational resources. Methodology. In the study, a questionnaire and a systematic analysis of the behavior pattern of users of educational resources in computer graphics were carried out (contextual research); functional and ergonomic analysis of educational resources in computer graphics was carried out. Results. It was found that electronic educational resources and modern multimedia and hypermedia technologies in the educational process can have different effects on educational achievements. Through the survey of users of educational resources on computer graphics, it was established that work and learning with the use of computer programs takes place not only at specially equipped workplaces, but also at home and in public places, mostly with portable computer equipment, in various positions, which causes inconvenience in case of using printed educational resources. The most common methods of learning new computer programs, the advantages and disadvantages of printed textbooks on computer graphics, as well as the most effective educational resources, tools, devices, elements (text, visual, sound) for learning new programs are determined. User requirements for educational resources on computer graphics have been formed. Scientific novelty. For the first time, the model of educational behavior of users of computer graphics educational resources was investigated; user ergonomic and communication requirements for relevant educational resources were defined. The practical significance of the obtained results lies in the possibility of their application for the development of more effective educational resources intended for studying computer graphics programs.